The degree of including assessment activities for the skill of creative flexibility in the Arabic language textbook for the twelfth grade in the Sultanate of Oman - Alshamsi, Wafa Salim Mohammed; Ali, Amal Mahmoud (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed at analyzing the content of the evaluation activities in the Arabic language course for the twelfth grade in the Sultanate of Oman in the light of the creative flexibility skill. A number of statistical methods and treatments were used in the study to reach the research results, such as: frequencies, percentages, and the (Holsti) equation to calculate the stability of the analysis tool. The study reached several results, most notably: The activities of the Arabic language course for the eleventh grade took into account the skill of flexibility with a weak degree of (17%). The study came out with several recommendations, the most important of which is directing those in charge of planning and authoring Arabic language curricula to take into account procedural definitions that accurately reflect the nature of the skill of flexibility, as stated in the educational literature, when building the activities of Arabic language curricula.